Potensi Pemulihan Terumbu Karang Dinilai Dari Indeks Kesehatan pada Kawasan Konservasi Tanjung Labu - Ferizal, Jemi; Sudarmo, Agnes Puspitasari; Susanto, Adi (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
The coral reef ecosystem is one of the ecosystems that functions as an important habitat for various marine species including coral reef fish, provides coastal protection, and supports economic activities such as fisheries and tourism. The study was conducted in March 2024 in the waters of Tanjung Labu, Bangka Selatan, precisely in Karang Kucek and Karang Tepi, with a total of 8 stations. This study aimed to determine the coral reef health index, diversity index, uniformity and dominance of coral reef fish, and the relationship between coral reefs and coral reef fish. The method of collecting coral reef data uses UPT (Underwater Photo Transect) and coral reef fish using UVC (Underwater Visual Census). The results of the study showed that the coral reef cover value in Tanjung Labu waters was classified as good with an average value of 51.14%, and coral fragments and fleshy seaweed algae were relatively low. The average coral reef health index value was 5.75, in the good range of 4-6 with high coral cover and good recovery potential. The community structure showed a low dominance index, moderate diversity, and uniformity indicating a labile community. Analysis of the relationship between coral reefs and coral reef fish shows a significant relationship, with a high correlation between the number of coral reef life form species and the number of individuals and biomass of coral reef fish. Public education and ongoing research are also important, with collaborative support from the government, organizations, and local communities for successful conservation.